Structure of macroinvertebrate communities in riffles of a Neotropical karst stream in the wet and dry seasons - Righi-Cavallaro,Karina Ocampo (2010)
AIM: Our study evaluated the effects of physical and chemical variables and seasonality on diversity and structure of the macroinvertebrate fauna in riffles of a Neotropical chalk stream; METHODS: Sampling was performed during the dry (September 2003) and rainy (March 2004) seasons, in five sites. Five samples were taken at each point with a Surber sampler. Physical and chemical variables were also evaluated; RESULTS: Temperature, pH, orthophosphate and total nitrogen were very similar for both seasons, while riffle length, conductivity, alkalinity, ammonia, phosphorus and leaf litter had different values. The total number of organisms collected was 25114 belonging to at least 50 families. Insects dominated in the samples. The highest abundance was found for the dry period. Temporary stretches were sampled in rainy season in order to complement the faunal inventory; CONCLUSIONS: The environmental seasonality was an important factor for structuring the macroinvertebrate fauna, with a significant difference between the invertebrate compositions in the sampling periods. The results of this study demonstrate the influences of seasonality on the temporal variation of communities.